Filosofi Makna Adil Dalam Pernikahan Poligami - Wahyu abdul jafar; Iim Fahimah (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2019)
This study explains in detail the question of fair meaning in polygamy marriages. So far, the meaning of fair is always different from everyone. Therefore, there is a need for a comprehensive study to decipher the issue of the meaning of scientific fairness. Substantive justice in Islam is always associated with the maker of the syara' (Allah). In relation to polygamy, The fair is a condition for a man to be allowed to do polygamy. justice aspects in polygamy is not an easy thing to do. Islam does not forbid or encourage let alone rule polygamy, this is because polygamy is a behavior that has existed since the time of ignorance and then tightened requirements in Islam. Islam is very strict in giving conditions until it is almost said not to be, because the argument contained in the Al Qur'an, maybe on fair terms but followed by another verse which says that